Profession-specific working conditions, burnout, engagement, and turnover intention: the case of Hungarian social workers - Győri, Ágnes; Ádám, Szilvia (Frontiers in Sociology, 2024)
IntroductionThis study investigated the interactions of profession-specific working conditions, burnout, engagement, and turnover intent among social workers in Hungary. Research on turnover among employees in human services occupations often overlooks the mechanism linking professional-specific factors with turnover intention.MethodsUsing a multistage stratified sampling method and cross-sectional design with a random sample of 664 participants, data were collected through computer-assisted personal interviews.ResultsThe findings revealed that poor working environments, workplace struggles, and profession-specific factors, such as challenges stemming from clients' difficult life situations, difficulties with client engagement, cultural disparities, and fieldwork-related challenges, significantly influenced turnover intentions. These factors not only directly affected professionals' intentions to leave but also had indirect effects through burnout and work engagement.DiscussionOur findings highlighted the importance of addressing both general and profession-specific working conditions to reduce turnover intention among social workers. Key challenges included clients' difficult life situations, cooperation with clients, cultural differences, and fieldwork difficulties. Overall, preparing social workers for real-life situations and related conflicts should be incorporated into their training.